Just Do It: High Intensity Physical Activity Preserves Mental and Physical Health in Elite and Non-elite Athletes During COVID-19 - Casali, Nicole; Cerea, Silvia; Moro, Tatiana; Paoli, Antonio; Ghisi, Marta (Frontiers in Psychology, 2021)
Background: The COVID-19 pandemic forced most Italian athletes to cease their regular training activities, with possible consequences on both mental and physical health. The present study aimed at assessing changes in Physical Activity (PA) from pre- to lockdown, and examining the relationships among lockdown PA, quality of life (mental and physical health), motivation to exercise, psychological distress, intolerance of uncertainty, and body dissatisfaction. Methods: A total of 204 athletes of different sports (91 elite; 110 females; mean age = 22.55, SD = 5.76) answered an online survey investigating demographics, sport-related questions, PA (IPAQ-S), quality of life (SF-12), and psychological variables (BREQ-2, DASS-21, IUS-R, and EDI-3-Body dissatisfaction subscale). Results: Both elite and non-elite athletes significantly reduced their PA intensity and volume (p < 0.001). Elite athletes did not differ from non-elite in terms of total PA intensity and hours of training during lockdown (p > 0.05). Elite and individual athletes showed higher intrinsic motivation to exercise compared to non-elite and team sports (p < 0.01). Female athletes displayed higher distress, worse mental health, and higher body dissatisfaction than males (p < 0.05). Mediation models showed that vigorous PA positively affected both mental (p < 0.05) and physical (p < 0.001) health during lockdown, independently of distress and intolerance of uncertainty. Conclusions: The COVID-19 lockdown was taxing for athletes, particularly professionals; those who were able to practice PA at high intensity during lockdown reported better mental and physical health.